The Politics of Permaculture - Leahy, Terry (Pluto Press, 2021)
Permaculture is an environmental movement that makes us reevaluate what it means to be sustainable. Through innovative agriculture and settlement design, the movement creates new communities that are harmonious with nature. It has grown from humble origins on a farm in 1970s Australia and flourished into a worldwide movement that confronts industrial capitalism. The Politics of Permaculture is one of the first books to unpack the theory and practice of this social movement that looks to challenge the status quo. Drawing upon the rich seam of publications and online communities from the movement as well as extensive interviews with permaculture practitioners and organisations from around the world, Leahy explains the ways permaculture is understood and practiced in different contexts. In the face of extreme environmental degradation and catastrophic climate change, we urgently need a new way of living.
English
Keywords: Conservation of the environment; Environmental policy & protocols; Environmental economics; Nature; Environmental Conservation & Protection; Political Science; Public Policy; Environmental Policy; Business & Economics; Environmental Economics